The Influence Of Emotional Marketing And Experiential Marketing On Purchasing Decisions In E-commerce tiktok shop (Case Study Of Uncip Students) - Imam Budi Darmawan; Isyana Rahayu (International Journal of Business and Quality Research, 2026)
This study aims to analyze the influence of Emotional Marketing and Experiential Marketing on consumer purchase decisions on the TikTok Shop e-commerce platform, with a case study on students of Cipasung University (UNCIP) Faculty of Economics and Business class of 2022. The research method used is quantitative descriptive with a verifiable approach. The sample amounted to 85 respondents who were selected using the purposive sampling technique based on the Slovin formula with an error rate of 10%. Data were collected through a five-point Likert scale questionnaire and analyzed using validity tests, reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation, and linearity), multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) with the help of SPSS version 26. The results showed that (1) Emotional Marketing had a positive and significant effect on purchase decisions (t = 2.074; sig. = 0.041); (2) Experiential Marketing has a positive and significant effect on purchase decisions (t = 6,953; sig. = 0.000); and (3) simultaneously, the two variables were able to explain 69.3% of the variation in purchasing decisions (R² = 0.693; F = 92,452; sig. = 0.000). These findings indicate that emotion- and experiential-based marketing strategies are crucial factors in driving young consumers' purchasing decisions on social commerce platforms.